Determination of Energy Usage and Greenhouse Gas Emissions in Lavender Production (Revista de Investigaciones Universidad del Quindío, 2022)
The purpose of this study is to reveal the energy usage and greenhouse gas emission in lavender production. The study has been conducted in 2022 in Center district of Kırklareli province in Turkey and covers the 2021-2022 production seasons. Agricultural inputs and outputs were calculated to calculate the energy use and greenhouse gas emissions in lavender production. According to the research results, the inputs are 5883.39 MJ ha-1 (59.30%) farmyard manure energy, 2425.51 MJ ha-1 (24.45%) diesel fuel energy, 732.02 MJ ha-1 (7.38%) chemical fertilizers energy, 421.89 MJ ha-1 (4.25%) machinery energy, 276.70 MJ ha-1 (2.79%) human labour energy, 97.31 MJ ha-1 (0.98%) transportation energy and 84.81 MJ ha-1 (0.85%), vermicompost energy, respectively. Total input and output energy were calculated as 9921.63 MJ ha-1 and 12859.77 MJ ha-1, respectively. Energy use efficiency (EUE), specific energy (SE), energy productivity (EP) and net energy (NE) were calculated as 1.30, 2.86 MJ kg-1, 0.35 kg MJ-1 and 2938.13 MJ ha-1, respectively. The total energy input can be classified as 27.24% direct, 72.76% indirect, 62.94% renewable and 37.06% non-renewable. GHG ratio value was calculated as 0.08 kg CO2-eqkg-1 in lavender production.
Keywords: Energy use efficiency; GHG ratio; Kırklareli; Lavender; Turkey